Simulation and Analysis of a Queueing System in a Pharmacy Division: A Case Study of a Private Hospital in Hat Yai, Songkhla Province - Chaiyakul , Noppadol; Engchuan , Panitporn; Masae, Makusee (Thai Industrial Engineering Network Journal, 2023)
This research studies a queuing system in a pharmacy division of a private hospital in Hat Yai, Songkhla Province, to improve the efficiency of the service system. This pharmacy division is a place where there are many visitors because it has to provide both inpatient and outpatient services, including payment services for those who need to receive medicine so that the patients spend a long time waiting to receive services. Therefore, it is necessary to improve the service even further. This research applies simulation using Arena software. According to the simulation of the service system (1) inside the pharmacy room and (2) outside the pharmacy room, the results showed that increasing the number of staffs and pharmacists was able to reduce the average total amount of time and waiting time the patients spent in the system. In case of the inside the pharmacy room, the scenario 3 (adding two pharmacists at the prescription verification point during 9.00-14.00) could reduce the average total amount of time from 19.01 minutes to 10.03 minutes, counted for 47.49% reduction. Similarly, the outside the pharmacy room, the scenario 3 (adding a staff at the payment point and a pharmacist at the receiving a medicine point during 9.00-14.00) could reduce the average amount of waiting time from 12.51 minutes to 3.80 minutes, counted for 69.62% reduction.